2019
DOI: 10.1038/s41598-019-47763-8
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomised Controlled Trial on the Effectiveness and Adherence of Modified Alternate-day Calorie Restriction in Improving Activity of Non-Alcoholic Fatty Liver Disease

Abstract: Currently, there is no effective therapy for non-alcoholic fatty liver disease (NAFLD), although intensive calorie restriction is typically recommended but dietary adherence is an issue. The current study aimed to determine the effectiveness and adherence of eight weeks of modified alternate-day calorie restriction (MACR) in the control of NAFLD activity. This was a randomized controlled trial with MACR as the intervention and normal habitual diet as control. The outcome measures were body mass index (BMI), bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 38 publications
(46 reference statements)
1
110
0
Order By: Relevance
“…The traditional methods of losing weight (such as the daily calorie restriction), although the effect is affirmative, the control and compliance are poor (41). Based on this foundation, intermittent fasting regimens, especially ADF protocols, are being proposed in many pieces of literature (9,19,(33)(34)(35)(36)(37). The important unsolved issue is whether the effects of ADF can play a role for people who want to lose weight.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional methods of losing weight (such as the daily calorie restriction), although the effect is affirmative, the control and compliance are poor (41). Based on this foundation, intermittent fasting regimens, especially ADF protocols, are being proposed in many pieces of literature (9,19,(33)(34)(35)(36)(37). The important unsolved issue is whether the effects of ADF can play a role for people who want to lose weight.…”
Section: Discussionmentioning
confidence: 99%
“…An 8 weeks modified alternate-day calorie restriction was found to lead to reductions in BMI, liver enzymes, liver steatosis and liver stiffness (based on shear wave elastography) compared to no intervention with adherence rates of 75-83%. 28 A larger trial comparing alternate-day and time-restricted feeding with a control group for 12 weeks revealed that both diets led to significant short-term reductions in weight and improvements in dyslipidaemia, although no changes were seen for fasting levels of insulin or liver stiffness. 29…”
Section: Randomized Controlled Trial Datamentioning
confidence: 99%
“…All six studies evaluated the impact of the dietary intervention on alanine aminotransferase (ALT) levels, but only half of these studies demonstrated a significant improvement (LGMD and INRAN, MD and LF and MACR). Patients achieved weight loss in all of these studies, with significant weight loss in 5/6 studies [22,25,26].…”
Section: Impact Of Diets On Hepatic Outcomesmentioning
confidence: 97%
“…On the basis of abstract review, 26 were selected for full-text review. Two study authors classified six articles as meeting the predefined criteria for analysis [17,[22][23][24][25][26]. A total of 317 patients from six unique populations were represented.…”
Section: Studies Included In the Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation